Identification of the right environmental KPIs for manufacturing operations: towards a continuous sustainability framework - Sherif, Ziyad; Sarfraz, Shoaib; Jolly, Mark R.; Salonitis, Konstantinos (MDPI, 2022)
Sustainable manufacturing has grown into a major subject of discussion between individuals and organisations around the world. This is attributed to the recognition of the urgency in advancing sustainable manufacturing due to the diminishing non-renewable resources, stricter regulations related to environmental impacts and the increasing consumer preference for environmental-friendly products. However, manufacturing companies have been confronted with a decision on which KPIs to select for appraising their processes, and how they should interpret these KPIs in transforming their processes towards a sustainable future. This paper presents a structured framework for the manufacturing industries to identify the right environmental KPIs. It includes building a database for environmental KPIs, categorising, ranking, and composing a final KPI set for specified targets. The developed method allows for the selection of the most effective KPI in representing a specified target as well as identifying unmonitored environmental aspects. The framework has been corroborated by subject matter and industry experts in which the potential benefits have been verified.
Keywords: sustainable manufacturing; indicators; environment; selection criteria